ChemInform Abstract: Ruthenium‐Catalyzed Intermolecular Direct Silylation of Unreactive C(sp3)—H Bonds. Issue 27 (16th June 2016) - Li, Wei; Huang, Xiaolei; You, Jingsong
Abstract: This is the first Ru‐catalyzed silylation of unreactive, aliphatic C(sp 3 )—H bonds.